BASIC CRITERIA FOR WELL-BEING LIFE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Well-being is a fundamental aspect of human existence, encompassing a range of dimensions that contribute to an individual's overall happiness and life satisfaction. This article explores the basic criteria for a well-being life, emphasizing physical, mental, and emotional health, as well as social connections, economic stability, and personal fulfillment. By examining various theories and models of well-being, the article identifies key factors that contribute to a balanced and healthy life. These include the importance of self-care, positive relationships, meaningful work, and financial security. It also highlights the role of societal structures in promoting well-being and suggests practical approaches individuals and communities can adopt to enhance their quality of life. The article concludes with recommendations for fostering an environment that supports well-being at both the individual and collective levels.